Diabetes gestacional: estrategias para su prevención - Romero Nagua, Sheyla Paulette (Machala : Universidad Técnica de Machala, 2024)
INTRODUCTION: It is the hyperglycemic state that is initially detected in pregnancy and is the most diagnosed metabolic condition during gestation due to the risk of complications for the maternal-fetal binomial and its offspring. According to world organizations, for every 7 pregnant women, one has elevated glucose levels and more than 80% are diagnosed with gestational diabetes. DEVELOPMENT: Gestational diabetes is a preventable disease if the factors involved are detected in a timely manner, being obesity the one that stands out the most, being present in 60% of adult women with 13% for gestational diabetes. In Ecuador it is among the first six causes of maternal-fetal death-disease, with a prevalence of almost 1,804 per 100,000 inhabitants. Therefore, the purpose of this study is to identify strategies for the early prevention of gestational diabetes for the benefit of the maternal-fetal binomial through the search for updated scientific articles that will reduce the number of newly diagnosed cases of gestational diabetes.
INTRODUCCION: Es el estado hiperglucémico que se detecta inicialmente en el embarazo y es la condición metabólica más diagnosticada durante la gestación por el riesgo de complicaciones para el binomio materno-fetal y su descendencia. Según las organizaciones mundiales, por cada 7 gestantes, una presenta niveles elevados de glucosa y mayor al 80% son diagnosticadas de diabetes gestacional. DESARROLLO: La diabetes gestacional es una enfermedad prevenible si se detecta oportunamente los factores involucrados, siendo la obesidad el que mayor destaca presentándose en el 60% de las mujeres adultas con el 13% para diabetes gestacional. En Ecuador está dentro de las primeras seis causas de enfermedad-muerte materno fetal, con una prevalencia de casi 1.804 por cada 100.000 habitantes. Por consiguiente, el propósito del presente trabajo es identificar estrategias para la prevención temprana de diabetes gestacional en beneficio del binomio materno fetal mediante la búsqueda de artículos científicos actualizados que permita reducir el número de casos nuevos diagnosticados de diabetes gestacional.
Keywords: DIABETES GESTACIONAL; RESISTENCIA A LA INSULINA; PREVENCION; FACTORES DE RIESGO